Blood Serum and Seminal Plasma Selenium, Total Antioxidant Capacity and Coenzyme Q10 Levels in Relation to Semen Parameters in Men with Idiopathic Infertility - ÇAKIR, NEŞE; BİNGÖL ÖZAKPINAR, ÖZLEM (HUMANA PRESS INC, 2014)
In this case-control study, we aimed to evaluate the serum and seminal plasma levels of Selenium (Se), total antioxidant capacity (TAC), and Coenzyme Q10 (CoQ-10) and determine their relationship with sperm concentration, motility, and morphology in men with idiopathic infertility. A total of 59 subjects were enrolled in the study. Forty four patients were diagnosed with idiopathic male infertility and had abnormal sperm parameters, and 15 subjects had normal sperm parameters with proven fertility. Serum Se, semen Se, and semen TAC levels were significantly different in the fertile and infertile groups (p < 0.01, p < 0.001, and p < 0.001, respectively). However, serum TAC, serum, and seminal plasma CoQ-10 levels did not differ between fertile and infertile groups. When the levels of the measured parameters were compared in serum and seminal plasma, serum levels of Se were found to be correlated positively with the semen levels in all subjects included into the study (N = 59) (r = 0.46, p < 0.01). A relationship was found between neither serum and semen levels of TAC nor between serum and semen levels of CoQ-10. Correlations among measured serum and semen parameters with sperm parameters demonstrated that both the serum and semen levels of Se were correlated positively with spermatozoa concentration, motility, and morphology. Additionally, seminal plasma levels of TAC correlated positively with all these sperm parameters. On the other hand, seminal plasma levels of CoQ-10 correlated only with sperm morphology but not with concentration or motility. No relationship was observed between serum levels of TAC or serum levels of CoQ-10 and sperm parameters. In conclusion, serum and seminal plasma Se deficiency may be a prominent determinant of abnormal sperm parameters and idiopathic male infertility. Measurement of serum Se levels may help determine nutritional status and antioxidant capacity in infertile patients, which may help distinguish those patients who will benefit from supplementation therapy.
Keywords: Selenium; Total antioxidant capacity; Coenzyme Q10; Male infertility; Spermatozoa; Serum and seminal plasma; OXIDATIVE STRESS; DOUBLE-BLIND; Q(10); QUALITY; SYSTEM